Kajian Penggunaan Xanthan Gum pada Roti Tawar Non Gluten yang Terbuat dari Maizena, Tepung Beras dan Tapioka - Faustine, Indah Kuswardani, Ch. Yayuk Trisnawati, (Jurnal Teknologi Pangan dan Gizi, 2008)
Bread is a cereal-based product, commonly from wheat flour and trough the process of mixing, fermentation, and baking steps until the changes in flavor, shape, and chemical composition occur. Wheat flour content gliadin and glutenin that form gluten which can cause an intestine inflammation in patients of celiac diseases. They should avoid to consume gluten so need gluten-free product such as gluten free bread. The Gluten-free bread made from rice flour, corn starch, and cassava starch with proportion of 74.2% cornstarch, 17.2% rice flour, and 8.6% cassava starch. In general gluten-free white bread has poor capability to retain gas from fermentation, so will has firm crumb, poor loaf and easy to be stahling. This condition can be improved by addition of hydrocolloid such as xanthan gum. Randomized Block Design (RBD) used in research. The treatment was concentration of xanthan gum 0.5%, 1%, 1.5%, 2%, and 2.5%. and repeated five times. Observation was done on water content, hardness, compressibility, specific volume, and preference tests for crumb pore, texture (mouthfeel), and moistness. The data were analyzed with Anova α = 5% and than continued with Duncan’s Multiple Range Test (DMRT) at α = 5% when the treatment gave significant influence. The best treatment is determined according to the Effectiveness Index. The result showed that the use of xanthan gum has no effect on the water content of bread, but influence the hardness, compressibility, specific volume, and sensory evaluation of gluten-free white bread made from cornstarch, rice flour, and cassava starch. The higher the concentration of xanthan gum results in higher value of hardness, compressibility, and specific volume of gluten-free bread. The treatment of 2% xanthan gum showed to give the best gluten free bread with 23.89% of water content, 23.8 N of hardness, 98.02% of compressibility, 2.1675 cm3/g of volume specific, and give the best score in preference test.